Niewiasta czy kobieta? : teologiczne nacechowanie passusów J 2, 4 oraz J 19, 26 we współczesnych przekładach Nowego Testamentu / Kalina Wojciechowska. - Wojciechowska, Kalina (1971- ).
Keywords: translation, woman, maiden, Mary - Mother of Jesus, mariology, New Testament, Gospel according to John, theologisation, confessionalisation.